Novel Molecular Approaches in Heart Failure: Seven Trans-Membrane Receptors Signaling in the Heart and Circulating Blood Leukocytes - Schiattarella, Gabriele Giacomo; Magliulo, Fabio; Cattaneo, Fabio; Gargiulo, Giuseppe; Sannino, Anna; Franzone, Anna; Oliveti, Marco; Perrino, Cinzia; Trimarco, Bruno; Esposito, Giovanni (Frontiers in Cardiovascular Medicine, 2015)
Heart failure (HF) is the result of molecular, cellular and structural changes induced by cardiac load or injury. A complex network of signaling pathways have been involved in the development and progression of cardiac dysfunction. In this review, we summarize the pivotal role of seven trans-membrane receptors (7TMR), also called G-protein coupled receptors (GPCRs), in HF. Moreover, we will discuss the current knowledge on the potential mirroring of 7TMR signaling between circulating blood leucocytes and the heart, and the related future possibilities in the management of HF patients.